THE IMPLEMENTATION OF TEAM COOPERATIVE LEARNING MODEL ON TEACHING THE PROCEDURE TEXT MATERIALS AT CLASS X SMAN 1 PALEMBANG - Aswadi Jaya (English Education Department at FKIP Nommensen University, 2023)
This study seeks to ascertain the effects of team cooperative learning of Team Games Tournament (TGT) learning model on procedural text material. Survey research is what this study falls under. In this research, students from class X at SMA Negeri 1 in Palembang served as the sample. The success of the learning model's implementation in the procedure text material, including the presentation stage, teams, games, tournaments, and team recognition, was the main focus of this study. Qualitative and quantitative data from the provided surveys were used to examine these topics. The study's findings regarding the application of the TGT learning paradigm to the Procedural Text material were quite positive as evidenced by the study's overall score on the Likert scale. Students find the application of this learning model to be quite appealing, but there are issues with it, including a lack of attention from teachers, a lack of learning tools, and a lack of a positive attitude when leading a group. Researcher believes that teachers need to prepare this learning paradigm with more maturity if they are to address the issues they have discovered